2010
DOI: 10.1179/106698110x12595770849605
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of an integrated neuromuscular inhibition technique on upper trapezius trigger points in subjects with non-specific neck pain: a randomized controlled trial

Abstract: Currently, large levels of practice variability exist regarding the clinical deactivation of trigger points. Manual physical therapy has been identified as a potential means of resolving active trigger points; however, to date the ideal treatment approach has yet to be elucidated. The purpose of this clinical trial was to compare the effects of two manual treatment regimens on individuals with upper trapezius trigger points. Sixty patients, 19-38 years of age with non-specific neck pain and upper trapezius tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 16 publications
(15 reference statements)
2
70
1
Order By: Relevance
“…35,46 TrP dry needling (TrPDN) is one proposed treatment method 15 that has been shown to reduce TrP-associated pain. 38,43 A recent meta-analysis concluded that there is grade A (high-level) evidence to support the use of TrPDN in patients with upperquarter myofascial pain, particularly chronic neck and shoulder pain.…”
Section: T T Conclusionmentioning
confidence: 99%
“…35,46 TrP dry needling (TrPDN) is one proposed treatment method 15 that has been shown to reduce TrP-associated pain. 38,43 A recent meta-analysis concluded that there is grade A (high-level) evidence to support the use of TrPDN in patients with upperquarter myofascial pain, particularly chronic neck and shoulder pain.…”
Section: T T Conclusionmentioning
confidence: 99%
“…This in turn leads to sympatho-excitation and activation of the periaqueductal gray matter, which plays a role in the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT descending modulation of pain. Owing to stimulation of the mechanoreceptors, simultaneous gating of the nociceptive impulses takes place in the dorsal horn of the spinal cord (27).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In addition, there is some evidence demonstrating that treatment of active MTrPs is effective for reducing symptoms in patients with mechanical neck pain. [10][11][12] These studies suggest that MTrPs can be involved in the genesis of mechanical neck pain.…”
mentioning
confidence: 94%